Glycerol electrooxidation on platinum-tin electrodeposited films: inducing changes in surface composition by cyclic voltammetry - Mello, Gisele A. B. (2017)
In this work, PtSn binary electrodeposits were prepared in three compositions and submitted to successive voltammetric cycles in presence of glycerol (1.0 mol L−1) in acidic media. Catalysts were characterized by energy dispersive X-ray analysis and X-ray photoelectron spectroscopy before and after the cycles being performed, in order to check eventual changes in their compositions during the process. Spectroscopic results show that surface compositions are sensibly richer in Sn than their bulk counterparts. Overall, PtSn catalysts show a poor initial catalytic activity toward glycerol electrooxidation. However, as the cycles succeed, the voltammetric responses increasingly resemble that of Pt, while the oxidation currents increase. Results are rationalized in terms of a continuous enrichment of the surface by Pt at the expenses of a loss of Sn. Moreover, when the electrochemical surface area (ECSA) is estimated by stripping of CO, it becomes evident that electrooxidation currents remain growing, even when the ECSA is decreased, which makes the gain in catalytic activity particularly relevant. Ultimately, from a broader perspective, our results suggest that catalytic surfaces with tunable features (such as surface composition and catalytic response) can be obtained by the application of easily executable electrochemical protocols.